Microstructural characterisation of rubber modified asphalt mixtures - Abdul Hassan, Norhidayah (2013)
Research to improve the performance of asphalt mixtures through the addition of crumb rubber using the dry process has continued worldwide because of its potential as a recycling option for used tires. For decades, dry mixed rubberised asphalt mixtures have performed inconsistently in field trials and laboratory evaluations. However, current research has revealed that the performance of asphalt mixtures is highly dependent on the characteristics of its internal structure or phase constituents. A comprehensive methodology has been developed in this study to characterise the microstructural properties of dry mixed rubberised asphalt mixtures and correlate them with the mixtures' macroscopic response to compression and fatigue. The proposed methodology combines a non-destructive imaging technique; X-ray Computed Tomography (CT) and image processing and image analysis procedures to quantify the properties of air voids and cracks as well as the rubber distributions within the rubberised asphalt specimen. A gap graded mixture of Hot Rolled Asphalt (HRA60/20) containing different percentages and gradings of crumb rubber particles was compared to a conventional mixture (unmodified or control mix). The results showed that the addition of crumb rubber affects the formation and distribution of air voids in an asphalt mixture. Correlations between the internal structural damage parameters and the mechanical behaviour of the asphalt mixtures were unanimous in concurring that adding rubber improves a mixture resistance to fatigue failure. The modulus of the asphalt mixtures at peak stress under compression reduced when the rubber was introduced into the mixture although in contrast, the image analysis showed less fracture within the tested specimen in comparison to the control mix. The imaging procedures developed in this text are recommended as a guide to characterise the internal structure of rubberised asphalt mixtures.